Abundance on Canvas: Cultivating Peace and Floral Expressions in Lida Sherafatmands Paintings - Ramin Hajianfard, Muhamad Firdaus Bin Ramli (Tanjung Malim, 2024)
Abundance on Canvas: Cultivating Peace and Floral Expressions in Lida Sherafatmands Paintings by Ramin Hajianfard, Muhamad Firdaus Bin Ramli